2020
DOI: 10.1186/s12859-020-03790-1
|View full text |Cite
|
Sign up to set email alerts
|

Correntropy induced loss based sparse robust graph regularized extreme learning machine for cancer classification

Abstract: Background As a machine learning method with high performance and excellent generalization ability, extreme learning machine (ELM) is gaining popularity in various studies. Various ELM-based methods for different fields have been proposed. However, the robustness to noise and outliers is always the main problem affecting the performance of ELM. Results In this paper, an integrated method named correntropy induced loss based sparse ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Besides these, there are also some classification models composed of hybrid methods. Ren et al [ 26 ] proposed an integrated method named correntropy-induced loss-based sparse robust graph regularized extreme learning machine and applied it to the classification and recognition of cancer samples. Gao et al [ 27 ] performed cancer classification based on SVM optimized by particle swarm optimization combined with artificial bee colony approaches, and the effectiveness of these methods was verified by the experimental results.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides these, there are also some classification models composed of hybrid methods. Ren et al [ 26 ] proposed an integrated method named correntropy-induced loss-based sparse robust graph regularized extreme learning machine and applied it to the classification and recognition of cancer samples. Gao et al [ 27 ] performed cancer classification based on SVM optimized by particle swarm optimization combined with artificial bee colony approaches, and the effectiveness of these methods was verified by the experimental results.…”
Section: Related Workmentioning
confidence: 99%
“…Gao et al [ 27 ] performed cancer classification based on SVM optimized by particle swarm optimization combined with artificial bee colony approaches, and the effectiveness of these methods was verified by the experimental results. In addition, with the continuous development of machine learning, many studies have shown that the application of ensemble learning to classification problems is often better than traditional classification algorithms and single classifiers, and it can also solve the problem of increased data volume and data diversification [ 23 , 26 ]. Therefore, a large number of classification models based on ensemble learning have been proposed.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…4 . Correntropy-induced loss functions 21 , 22 were used to determine the weight ω, so as to improve the robustness.…”
Section: Related Work and Methodologymentioning
confidence: 99%
“…In subfigure (b) of panel (2) of Figure 1, the zoomed-in window displays overlapping regions on chosen patches. To learn relevant features, we employ a sparse coding and dictionary learning method with an l1-regularized correntropy loss function [71][72][73][74] named Correntropy-induced Sparse-coding (CS), which is expected to improve the computational efficiency compared to Stochastic Coordinate Coding (SCC) [75]. Outliers may be removed with the use of the correntropy loss function [71][72][73][74], the impact of non-Gaussian noise on the data will be lessened by using the correntropy measure as a loss function.…”
Section: Surface Feature Dimensionality Reductionmentioning
confidence: 99%